2010
DOI: 10.1017/s1751731109991467
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quality changes in udder quarter milk from cows with low-to-moderate somatic cell counts

Abstract: Much emphasis has been put on evaluating alterations in milk composition caused by clinical and subclinical mastitis. However, little is known about changes in milk composition during subclinical mastitis in individual udder quarters with a low-tomoderate increase in milk somatic cell count (SCC). This information is needed to decide whether milk from individual udder quarters with a moderate-to-high increase in milk SCC should be separated or not. The aim of this study was to determine how milk composition in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
23

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 36 publications
3
35
0
23
Order By: Relevance
“…After gently suspending each sample, the milk was poured into a separate, unused container. As previously indicated, 16 a composite milk sample representing one udder was created; this sample was comprised of all four quarters in one collection vial. A subsample of 15 ml of milk, taken from the composite milk sample, was transferred to sterile universal bottles.…”
Section: Sample Collectionmentioning
confidence: 99%
“…After gently suspending each sample, the milk was poured into a separate, unused container. As previously indicated, 16 a composite milk sample representing one udder was created; this sample was comprised of all four quarters in one collection vial. A subsample of 15 ml of milk, taken from the composite milk sample, was transferred to sterile universal bottles.…”
Section: Sample Collectionmentioning
confidence: 99%
“…In order to characterize milk quality, the most commonly used criteria are hygiene milk composition, and sensory characteristics of consumer interest (BRANDT et al, 2010). The main factors that affect raw milk quality are the prevalence of subclinical mastitis, hygiene conditions, and storage during milk production and processing (FORSBÄCK et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that milk samples collected from infected quarters contain more total protein and whey protein and less casein and lactose in comparison to healthy quarters (Kitchen, 1981;Cinar et al, 2015;Neitzel et al, 2015). During mastitis, increase in permeability of the blood-milk barrier also results in *0: 0-17,000 (cell/ml), 1: 18,000-34,000, 2: 35,000-70,000, 3: 71,000-140,000, 4: 141,000-282,000, 5: 283,000-565,000, 6: 566,000-1,130,000, 7: 1,131,000-2,262,000, 8: 2,263,000-4,525,000, 9: 4,526,000-and above; All the differences were significant at p < 0.0001; a, b an influx of serum proteins and enzymes from the blood, which may lead to increased proteolysis (Forsbäck et al, 2010). Reports on aforementioned research (Bansal et al, 2005;Forsbäck et al, 2010;Malek dos Reis et al, 2013) showed change in milk composition of infected quarters (including change in level of casein, decrease in α-casein and β-casein due to either proteolytic activity of enzymes or decreased casein synthesis in affected udder quarters, and increase in whey proteins) in comparison to milk produced by healthy quarters.…”
Section: Resultsmentioning
confidence: 95%
“…During mastitis, increase in permeability of the blood-milk barrier also results in *0: 0-17,000 (cell/ml), 1: 18,000-34,000, 2: 35,000-70,000, 3: 71,000-140,000, 4: 141,000-282,000, 5: 283,000-565,000, 6: 566,000-1,130,000, 7: 1,131,000-2,262,000, 8: 2,263,000-4,525,000, 9: 4,526,000-and above; All the differences were significant at p < 0.0001; a, b an influx of serum proteins and enzymes from the blood, which may lead to increased proteolysis (Forsbäck et al, 2010). Reports on aforementioned research (Bansal et al, 2005;Forsbäck et al, 2010;Malek dos Reis et al, 2013) showed change in milk composition of infected quarters (including change in level of casein, decrease in α-casein and β-casein due to either proteolytic activity of enzymes or decreased casein synthesis in affected udder quarters, and increase in whey proteins) in comparison to milk produced by healthy quarters. Regarding to the previous reports and results of this study, it can be concluded that permeability of basal lamina is higher either in young animals or in early stages of lactation because of higher milk protein percentage and SCS in both lower lactations and early stages of lactation.…”
Section: Resultsmentioning
confidence: 95%